Case studies on organic Rankine cycle hybrid systems for energy-efficient buildings - Sabbah Ataya; Abanob Joseph; M. Ismail; Swellam W. Sharshir (Case Studies in Thermal Engineering, 2025)
Integrating Organic Rankine Cycle (ORC) technology in building systems works as a feasible path for delivering energy-saving, environmentally friendly, Net Zero Energy Buildings (NZEBs) and Positive Energy Buildings (PEBs). This comprehensive review explores ORC applications in residential and commercial buildings, demonstrating a remarkable potential for energy conservation and emissions reduction through integration with renewable sources such as solar thermal, photovoltaic, and biomass systems. Exciting evidence supports ORC's effectiveness: A heat pump/ORC hybrid system with a 138.8 m2 solar thermal roof generated 3012 kWh/year, surpassing building consumption of 2318 kWh/year, achieving 4.2 % ORC efficiency. Similarly, a solar-powered ORC air-conditioning system demonstrated about 97 % reduction in energy requirements, yielding annual savings of $2010. A biomass solar hybrid ORC system successfully met 97.1 % of heating demands and 25.85 % of electricity needs, with 53.33 % operational efficiency. The study further explores ORC-based Combined Heat and Power and trigeneration systems, where regenerative flow turbines achieved isentropic efficiencies of 4.97–14.52 %. These findings underscore ORC technology's key role in advancing sustainable building practices and global decarbonization efforts when optimally integrated with renewable energy sources.